2019
DOI: 10.3390/ijms20163960
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cellular Metabolism Modulates Head and Neck Oncogenesis

Abstract: Considering the great energy and biomass demand for cell survival, cancer cells exhibit unique metabolic signatures compared to normal cells. Head and neck squamous cell carcinoma (HNSCC) is one of the most prevalent neoplasms worldwide. Recent findings have shown that environmental challenges, as well as intrinsic metabolic manipulations, could modulate HNSCC experimentally and serve as clinic prognostic indicators, suggesting that a better understanding of dynamic metabolic changes during HNSCC development c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 223 publications
(233 reference statements)
1
20
0
Order By: Relevance
“…Previous studies have sought to target different cancer-specific metabolic pathways, in particular glycolysis, for development of antitumor treatments (6)(7)(8)(9). There are three irreversible reactions in glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have sought to target different cancer-specific metabolic pathways, in particular glycolysis, for development of antitumor treatments (6)(7)(8)(9). There are three irreversible reactions in glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on cellular metabolism in SCCHN have revealed dysregulation in multiple metabolic pathways in tumors, such as the mitochondrial oxidative phosphorylation and the tricarboxylic acid cycle [ 10 ], and in the utilization of glucose as a dominant energy source for the survival and proliferation of SCCHN cells [ 11 ]. Despite the endeavors in targeting aerobic glycolysis in the treatment of SCCHN, no glycolytic inhibitors have been used in the clinical setting so far [ 12 ], suggesting that SCCHN cells might have alternative metabolic pathways to acquire energy to survive. Our previous study, and a study by another group, have shown that overexpression of phosphorylated inhibitory ACC1 or ACC2 was associated with a decreased survival rate in SCCHN [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells have been reported to have altered metabolism in glycolysis, which is called the "Warburg effect", and several other metabolic pathways are yet to be elucidated. Accumulated evidence has shown that the host-environmental manipulations could modulate the metabolism in OSCC and potentially serve as clinic prognostic indicators or developing adjuvant anti-cancer therapy [12]. Metabolomics may be a comprehensive approach to clarify the entire metabolic system that plays a role in OSCC.…”
Section: Introductionmentioning
confidence: 99%